Tindak Pidana Cyberbullying Terhadap Anak Melalui Platform Tiktok Perspektif UU ITE dan Hukum Pidana Islam - Farhan Mardiansah; Didi Sumardi; Yusup Azazy (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2026)
The rapid expansion of TikTok has simultaneously expanded social interaction and heightened the risk of cyberbullying targeting minors. This study examines cyberbullying in the form of physical mockery in TikTok comment sections using the case of Betrand Peto Putra Onsu as a concrete illustration through two complementary normative frameworks: Law Number 19 of 2016 on Electronic Information and Transactions (ITE Law) and Islamic Criminal Law (fiqh jinayah). Normative legal research with statutory, conceptual, and comparative law approaches was employed. Findings indicate that physical defamation in TikTok comment sections satisfies the elements of Article 27(3) of the ITE Law and qualifies as jarimah ta'zir under Islamic criminal law. The applicable ta'zir sanction is flexible yet firm, encompassing financial penalties, imprisonment, and victim restoration as an inseparable whole. The study recommends synergy between positive legal instruments and Islamic legal values to strengthen child protection in digital spaces.